Advancing allergy practice in India for respiratory physician - Shambo S. Samajdar; Saibal Moitra (The Journal of Association of Chest Physicians)
The landscape of allergy practice in India is undergoing transformative changes, shifting from traditional symptom management to embracing advanced diagnostic and therapeutic modalities for disease modification. This evolution is propelled by the integration of subcutaneous immunotherapy, biologic treatments, and the exploration of probiotics, alongside advancements in diagnostic approaches such as component-resolved diagnostics (CRD) and basophil activation tests. Despite the promising potential of these innovations to enhance patient care, their implementation faces challenges, including limited awareness, safety concerns, accessibility, and affordability. Moreover, the development and standardization of allergy diagnostics, such as CRD, along with the establishment of regional pollen calendars, are crucial for improving the precision of allergy care. This abstract underscores the need for overcoming existing barriers and leveraging emerging technologies and treatments to significantly improve the management of allergic diseases in India, aiming for a future where allergies are not just managed but effectively controlled and prevented.